2011
DOI: 10.1111/j.1365-2575.2011.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

The DySIIM model for managing IS integration in mergers and acquisitions

Abstract: Corporate mergers and acquisitions (M&As) are prominent means for corporate strategy. In many M&As information systems (IS), integration is critical for achieving the intended goals. By integrating previous research on M&A and IS integration, we develop a six-dimensional theoretical framework for IS integration in corporate M&As. The framework is used to describe and explain IS integration management in four M&As. Based on the four cases, the theoretical framework and the existing literature, an initial model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Although prior studies (Alaranta & Kautz, 2007;Chao & Lin, 2009;Halonen et al, 2009) have suggested that environmental factors affect platform development, our study enhances this literature by identifying the challenges that result from these factors, which in turn are addressed by strategies used in the focal organization. Our findings also confirm some aspects of the dynamic system of IS integration in M&A situations that was developed by Henningsson & Carlsson (2011). For example, our study highlights how the potential of IS to provide synergy was initially not recognized by the majority of the stakeholders.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although prior studies (Alaranta & Kautz, 2007;Chao & Lin, 2009;Halonen et al, 2009) have suggested that environmental factors affect platform development, our study enhances this literature by identifying the challenges that result from these factors, which in turn are addressed by strategies used in the focal organization. Our findings also confirm some aspects of the dynamic system of IS integration in M&A situations that was developed by Henningsson & Carlsson (2011). For example, our study highlights how the potential of IS to provide synergy was initially not recognized by the majority of the stakeholders.…”
Section: Discussionsupporting
confidence: 87%
“…This evolution was facilitated by the boundary spanning activities carried out in the platform development process. Thus our study suggests an additional link between synergistic potential and intentions and reactions not included in the DySIIM model (Henningsson & Carlsson, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…These assumptions are often not valid for transfer of IT capabilities between acquirers and targets in M&A for two reasons. First, the pervasive IT integration challenges and failures observed in M&A integrations indicate that IT capability transfers are difficult and costly (Merali & McKiernan, 1993;Johnston & Yetton, 1996;Wijnhoven et al, 2006;Mehta & Hirschheim, 2007;Henningsson & Carlsson, 2011;Tanriverdi & Du, 2011a, b). A survey by PricewaterhouseCoopers finds that about 83% of acquirers are not able to integrate IT (Shay, 2002).…”
Section: Hypotheses Developmentmentioning
confidence: 97%
“…That is, acquirers can transfer their superior capabilities to targets without having to endure much difficulty or incur significant costs. However, the IS literature on IT M&A integrations indicates that integrating IT capabilities of acquirer and target in M&A is notoriously difficult and costly (Merali & McKiernan, 1993;Johnston & Yetton, 1996;Wijnhoven et al, 2006;Mehta & Hirschheim, 2007;Henningsson & Carlsson, 2011;Tanriverdi & Du, 2011a, b). These difficulties indicate that IT capabilities are often not scale-free in M&A.…”
Section: Introductionmentioning
confidence: 97%
“…There is a body of work that has started to explore IS integration in the context of corporate M&A. Some of the findings relevant to the IS discipline include the recognition of the importance of IS integration during mergers (Buck-Lew et al, 1992;McKiernan & Merali, 1995), factors that contribute to the likelihood of successful integration (Stylianou et al, 1996;Robbins & Stylianou, 1999), such as IS integration strategy (Henningsson & Yetton, 2013), the importance of learning and experience (Haleblian & Finkelstein, 1999;, the need for integration methods and tools (Alaranta & Henningsson, 2008;Henningsson & Carlsson, 2011), and the need for alignment between IS strategy and the M&A strategy (Wijnhoven et al, 2006;Mehta & Hirschheim, 2007;Baker & Niederman, 2014). This literature served as the backdrop for this issue.…”
mentioning
confidence: 99%